Representation of Religion in Nepali Brihat Shabdakosh- (2075) - Dr Bimala Sharma, (The Creative Launcher, 2021)
Nepali Brihat Shabdakosh (2075 B. S), claims that it has selected those lexical items which are available in the Nepali speech communities. This article contends the claim and proposes of lexicographers’ ideology guides the content of the dictionary. It focuses on: How different religions/religious people are named and referred to linguistically? What kind of religious traits, features, qualities and features are ascribed to them? How are the lexical items related to religion are explained, defined and presented? To meet the objectives, it implies qualitative approach and uses content analysis method to exhibit the disproportional representation of religions in the Kosh. Swatantra Varna 'Ra' is selected for this purpose. Critical discourse analysis is used as a tool to scrutinize the lexical items. Primarily all the lexical items under the Swatantra Varna 'Ra' are studied and a list of lexicons related to all religions is prepared. Then the selected lexicons are scrutinized from the lenses of critical discourse analysis to meet the objectives of the study. The findings establish the fact that Hinduism is overlexicalized and other religions are excluded, misrepresented, backgrounded, underlexicalized/overlexicalized, intensified and mitigated. This signifies that the whole Kosh-2075 reflects the psyche of Hindu Brahmin upper-class lexicographers.